Brown skua Catharacta antarctica breeding distribution and population trends on sub-Antarctic Marion Island, 1987–2023: implications of alien invasive species - Michelle M. Risi; Christopher W. Jones; Maëlle Connan; Eleanor A. Weideman; Lucy K. Smyth; Mia Cerfonteyn; Stephen Hunter; Peter G. Ryan (Polar Biology, 2026)
Predator-prey relationships on islands are often profoundly altered by invasive species. Brown skuas Catharacta antarctica are predator-scavengers at sub-Antarctic islands, where their population dynamics are linked to food availability. On Marion Island, skua population size and breeding distribution appear to have shifted in response to changes in burrowing petrel populations, which were severely impacted by feral cat Felis catus predation before cats were eradicated in 1991. We compare estimates of brown skua population size, breeding distribution, and fledgling production on Marion Island from studies conducted between 2010 and 2023 to earlier studies before cats were eradicated, including an extensive survey in 1987–1988. With increased search effort in 2023, we recorded 983 breeding territories, exceeding the 1987–1988 estimate of 878 territories, despite a slight decrease in average production, from 1.26 fledglings per pair per year in 1987–1988 to 1.10 between 2010 and 2022 ( n = 3 surveys). Most notably, there has been a shift in the distribution of breeding sites: territories in coastal areas where skuas mainly prey on penguins have increased by 39% since 1987–1988, whereas they decreased by 31% at inland sites where petrels are the main prey. This coastward shift is surprising given the modest recovery in petrel numbers since cats were eradicated and recent decreases in penguin populations. These counterintuitive findings establish a baseline for monitoring ecological change on Marion Island. As we expect more impacts associated with climate change, highly pathogenic avian influenza and invasive species management, regular surveys of predators such as brown skuas become increasingly valuable.